Corporate performance and the measures of value added - Petravičius, Tomas; Tamošiūnienė, Rima (Transport, 2008)
In recent years, managers have turned their attention to the ways increasing the value of their companies. A number of competing measures have been developed and marketed by investment and consulting firms. This paper considers the ways in which value can be created or destroyed in a firm and looks at how to calculate the cost of capital used to measure the opportunity cost of investing funds in one particular business instead of others with equivalent risk. Next, we have a look at the four most widely used value enhancement measures including Economic Value Added, Cash Flow Return on Investment, Market Value Added, Cash Value Added and use an example to think of where these approaches yield similar results and where differences might occur. In conclusion, we summarize the new or unique points in these competing measures, establish the information they can give and explain how to use it when managing and creating shareholder value. First published online: 27 Oct 2010